Strengthening Purity: Moral Purity as a Mediator of Direct and Extended Cross-Group Friendships on Sexual Prejudice. Issue 6 (12th May 2017) - Vezzali, Loris; Brambilla, Marco; Giovannini, Dino; Paolo Colucci, Francesco
ABSTRACT: The present research investigated whether enhanced perceptions of moral purity drive the effects of intergroup cross-group friendships on the intentions to interact with homosexuals. High-school students ( N = 639) reported their direct and extended cross-group friendships with homosexuals as well as their beliefs regarding the moral character of the sexual minority. Participants further reported their desire to interact with homosexuals in the future. Results showed that both face-to-face encounters and extended contact with homosexuals increased their perceived moral purity, which in turn fostered more positive behavioral intentions. Results further revealed the specific role of moral purity in this sense, as differential perceptions along other moral domains (autonomy and community) had no mediation effects on behavioral tendencies toward homosexuals. The importance of these findings for improving intergroup relations is discussed, together with the importance of integrating research on intergroup contact and morality.